USING RESEARCH AND PROJECT ACTIVITY AS AN EFFECTIVE FORM TEACHING (International Conference on Educational Discoveries and Humanities, 2025)
The article reveals the problem of using research and design activities of students in a foreign language lessons. Moreover, comparative analysis of the content of two concepts of research and project activities is discussed. The functions of research and design activities are considered. Special attention in the article focuses on ways of developing activity in the modern system education and its place among other effective methods.